[Bis(3, 5‐diisopropylpyrazol‐1‐yl‐κN2)dihydroborato](triphenylphosphane‐κP)copper(I). (5th August 2013) - Fujisawa, Kiyoshi; Noguchi, Naoto; Noguchi, Yuki; Lehnert, Nicolai
<x xml:space="preserve">Abstract</x> In the title compound, [Cu(C18H32BN4)(C18H15P)], the CuI ion is coordinated by two N atoms from the anionic bidentate chelating bis(3, 5‐diisopropylpyrazol‐1‐yl)dihydroborate ligand [average Cu—N distance = 1.994 (3) Å] and the P atom from a triphenylphosphane ligand [Cu—P distance = 2.1676 (8) Å] in a trigonal geometry [the sum of the angles around the CuI atom is 359.6 (1)°]. The N—Cu—N angle between adjacent coordinated pyrazole‐ring N atoms is 98.99 (9)°, while the average N—Cu—P angle between the coordinated pyrazole N atom and the triphenylphosphane P atom is 130.3 (1)°.